2004
DOI: 10.1007/bf03173237
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic assessment of literacy: English as a third language

Abstract: The aim of this paper is to valuate the applicability of Vygotsky's sociocultural theory and the concept of dynamic assessment to the problem of assessing reading comprehension in English as a third language (L3). The study was conducted with immigrant students from Ethiopia studying at pre-academic centers in Israel. The assessment procedure included a pre-test, mediation, and post-test. The pre-test was based on a standard reading comprehension placement exam. Based upon the pre-test material, a very detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…There is now a common consensus among language educators on the significance of the role played by assessment in teaching activities and outcomes (Kozulin & Garb, 2004). However, simultaneous with the developments in the teaching techniques and theories (Zaker, 2015(Zaker, , 2016, the summative assessment approach which adopts a time-bound and narrow approach to assessment has been under serious attack (Garrison & Ehringhaus, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is now a common consensus among language educators on the significance of the role played by assessment in teaching activities and outcomes (Kozulin & Garb, 2004). However, simultaneous with the developments in the teaching techniques and theories (Zaker, 2015(Zaker, , 2016, the summative assessment approach which adopts a time-bound and narrow approach to assessment has been under serious attack (Garrison & Ehringhaus, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Systematic studies are required for confirming the advantage of portfolio assessment approach over the traditional summative approach which cannot provide the immediate and contextualized feedback helpful for teachers and students during the learning process (Kozulin & Garb, 2004). Moreover, it is of outmost importance to inspect the way portfolio assessment affects EFL learners' internal factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the fact that mediation in general improved the overall performance of test takers, LPS scores indicated that different test takers benefited from mediation in different degrees. Kozulin and Garb (2004) classified LPS scores in three categories: high (≥ 1), mid (.71-.8) and low (≤ .70). The lowest and highest LPS scores in this study were .75 and 1.20, respectively.…”
Section: Internationalmentioning
confidence: 99%
“…In other words, instead of focusing on students' current knowledge and skills, dynamic procedures stress students' potential for learning and explore ways to realize those potentials (Kozulin & Garb, 2004). Proponents of DA (Elliot, 2003;Kozulin & Garb, 2004;Lidz & Elliot, 2006;Poehner & Lantolf, 2013;Shabani, 2014;Wang, 2015) claim that DA procedures are both feasible and effective for obtaining information about students' learning potential. DA procedures can better differentiate students concerning their gain of new text comprehension strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Definitions of the dynamic assessment (e.g. Kozulin & Garb, 2004;Sternberg & Grigorenko, 2002) have two constant aspects-active intervention by examiners and assessment of the response to intervention, which means the effect of mediational learning (Haywood & Lidz, 2007, p. 1).…”
Section: Dynamic Assessmentmentioning
confidence: 99%